2010
DOI: 10.1152/ajpendo.00058.2010
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced gestational androgen excess disrupts glucoregulation in rhesus monkey dams and their female offspring

Abstract: Discrete fetal androgen excess during early gestation in rhesus monkeys (Macaca mulatta) promotes endocrine antecedents of adult polycystic ovary syndrome (PCOS)-like traits in female offspring. Because developmental changes promoting such PCOS-like metabolic dysfunction remain unclear, the present study examined time-mated, gravid rhesus monkeys with female fetuses, of which nine gravid females received 15 mg of testosterone propionate (TP) subcutaneously daily from 40 to 80 days (first to second trimesters) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 78 publications
(115 reference statements)
3
93
0
Order By: Relevance
“…It is known that both the embryo development stages and early postnatal life period are crucial to condition adult health life. Thus, currently used PCOS animal models focus on these critical development time windows (Manikkam et al 2006, Demissie et al 2008, Abbott et al 2010, Amalfi et al 2012, Jang et al 2015. Furthermore, the metabolic and endocrine alterations found in the prenatal models lead to several long-term effects, thus highlighting the importance of the in utero environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that both the embryo development stages and early postnatal life period are crucial to condition adult health life. Thus, currently used PCOS animal models focus on these critical development time windows (Manikkam et al 2006, Demissie et al 2008, Abbott et al 2010, Amalfi et al 2012, Jang et al 2015. Furthermore, the metabolic and endocrine alterations found in the prenatal models lead to several long-term effects, thus highlighting the importance of the in utero environment.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS etiology remains controversial, and current theories emphasize on genetic and intrauterine origins coupled with environmental factors such as diet and altered lifestyle patterns (Franks 1995). It has been reported that prenatal androgen exposure is able to induce polycystic ovaries in rats (Demissie et al 2008, monkeys (Abbott et al 2010) and sheep (Manikkam et al 2006) and that fetal programming, mediated by prenatal hyperandrogenism, is related to hyperinsulinemia, dyslipidemia, insulin resistance (IR), cardiovascular disease and metabolic syndrome (Demissie et al 2008, Amalfi et al 2012, Heber et al 2013. However, how fetal programming impacts on different tissues is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest a complex relationship between the altered maternal environment and fetal growth in PCOS. The mechanisms leading to the development of PCOS are largely unknown, but the pathogenesis of PCOS is likely to include a combination of genetic and epigenetic factors (51) as well as environmental influences (2).…”
mentioning
confidence: 99%
“…These findings indicate that the effects of prenatal androgenization on the placenta, fetus, and female offspring are not caused by changes in maternal metabolism. On the other hand, in monkeys, maternal androgen administration during pregnancy does increase weight gain and alters insulin and glucose responses to glucose and increases conjugated estrogen of the dam, indicating that effects in female offspring may be caused by altered maternal metabolism (2). The placenta normally acts as a barrier that protects the fetus from excessive maternal androgens.…”
mentioning
confidence: 99%
“…Foetuses of animals exposed to androgen excess at the beginning of pregnancy may also exhibit an increased risk of hyperinsulinaemia and visceral obesity in infancy (Escobar-Morreale et al 2014). Although developmental programming by androgen excess might be associated with IUGR in rodents (Sathishkumar et al 2011) and sheep (Beckett et al 2014) and with low birth weight (LBW), these characteristics are not frequently found in that process in non-human primate models for PCOS (Abbott et al 2010). LH, luteinising hormone.…”
Section: Developmental Programming Related To Pcos Manifestations: Asmentioning
confidence: 99%